Divided Alliances: A Discussion of Inuit Resilience in Post-Secondary Education - Snow, Kathy; Obed, Diane; Lane, Jodie (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
Although the Inuit high school completion rate has been climbing, the same cannot be said for Inuit participation in post-secondary education in Canada. This paper seeks to move beyond the obvious physical, and financial barriers to explore the colonial biases present in post-secondary institutions as further and more enduring challenges to access for Inuit. Through conversations with 10 Inuit post-secondary participants, graduates, and leavers, seven critical factors emerged. Viewed from the perspective of Inuit Qaujimajatuqangit, these factors identified where institutions have continued to fail students. The hope here is to raise greater awareness of the unparalleled challenges Inuit must face when choosing to participate in post-secondary education not only in terms of leaving home, but also of negotiating culture and the worldviews of Southern colonial learning institutions.